FROM THE MOBILIZATION OF THE UNEMPLOYED TO THE FORMATION OF A NEW SOCIO-POLITICAL ACTOR (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
This article traces the trajectory of the unemployed movements as a growing socio-political actor in Argentine contemporary politics. Ignored by the trade unions, neglected by the authorities, workers expelled from the labor market by the neoliberal reforms took to the roads in the late 1990s in order to give visibility to their grievances and demand solutions. Since then, through the use of protest, they have been able to establish a bargaining arena with the authorities for the allocation of unemployed compensations. The article explores the role played by external actors –political activists, ex-unions militants, members of the ngos– in the process of the organization of the unemployed, the effects of government policy responses on their levels of mobilization, and the influence of changes in the political context on the success of collective action.
Keywords: Market reforms, Unemployed, Collective action, Conditional cash transfers